Antibiogram of bacterial isolates obtained from infants and children at the University of Calabar Teaching Hospital (UCTH). - Emmanuel Onyekachukwu Ibeneme , Zenoh Danjuma Ali * , Glory Philemon Bebia , Joy Chinweokwu Ezema , JosephusBoniface. (Sokoto Journal of Medical Laboratory Science)
The gradual increase in antimicrobial resistance in children is a major challenge in the field of hospital epidemiology and medical microbiology. This study was conducted to investigate the susceptibility pattern of commonly used antimicrobial agents against bacterial isolates in children attending UCTH. Fifty clinical specimens; blood, urine, eye, ear and wound swap were collected from infants and children 1-day old to 9 years. About 2mL of the blood was dispensed into Brain Heart infusion broth (10ml) contained in a Bijou bottle and incubated for 2 days at 37°C. Midstream urine samples were collected into sterile universal containers and cultured on blood and CLED agar using the Leigh and Williams paper strip method, while sterile swab-stick was used to collect ear and eye specimen (discharge). The ear specimens were cultured on CLED and blood agar while the eye swap on CLED and chocolate agar. Isolates susceptibility was tested on gentamicin, erythromycin, Zithromax, ampicillin, amoxicillin and penicillin using disc diffusion method by Kirby-Bauer. Of the 50 subjects examined, a total of 39 bacterial isolates were obtained from the 36(72%) culture positive samples. S. aureus was the most isolated 22(56.4%), followed by P. aeruginosa 7(17.9%), Streptococci, Coliform, and Proteus were 3(7.7%), 6(15.4%) and 1(2.6%) respectively. Female children had more bacterial isolates 19(73.1%) compared to male 17(70.1%). The isolates were more sensitive to gentamicin 25(64%), followed by zithromax 23(59%), erythromycin 16(41%) and ampicillin 12(31%). The isolates were less sensitive to Penicillin 2(5) and Amoxicillin 10(26), multi resistance was seen in 14(35.9%) of the isolates. Resistance to antibiotics is on the rise and babies are particularly at increased risk because of lower immunity. The study recommends the need for the development of alternative therapy.